Redirecting EFL writing instruction through mind mapping technique in senior high school - Besral Besral; Sari Yustina Luli; Yola Veranita Putri (Journal of Research on English and Language Learning (J-REaLL), 2020)
The purpose of this research was to see the effects of Mind Mapping Technique toward students' writing ability especially in writing descriptive text. The results of Post-test experiment and control class were used to confirm the hypothesis. The population of this research was all of the students at X grade of Senior High School 3 Padang Panjang, consisting of 96 students who spread in 3 classes. Two classes were taken as sample by using cluster random sampling. Writing test was used to collect the data. The treatments were done in six meetings. The data of this research were analyzed by using Statistical Product and Service Solution (SPSS) Program. The result showed that the mean score of students' post-test at experimental class was (65.94) higher than those of control class (58.16). The calculation of the test showed that t-calculate was (8.27) higher than t-table (1.67) at the significant level of .05 meaning that students who were taught through Mind Mapping technique produced better writing skills in descriptive text. It can be concluded that teaching writing by using mind mapping technique gave significant difference on students' writing ability at X grade of Senior High School 3 Padang Panjang. Therefore it is recommended that English teachers should use this technique to improve students' writing ability.